Quality of Mesorectal Excision ("Plane of Surgery") - Which Quality Targets are Adequate? - Hermanek, Peter; Merkel, Susanne; Ptok, H.; Hohenberger, Werner (Zentralblatt für Chirurgie, 2015)
Today, the examination of rectal cancer specimens includes the obligate macroscopic assessment of the quality of mesorectal excision by the pathologist reporting the plane of surgery. The frequency of operations in the muscularis propria plane of surgery (earlier described as incomplete mesorectal excision) is essential. The quality of mesorectal excision is important for the prognosis, especially as local recurrences are observed more frequently after operations in the muscularis propria plane of surgery. For the definition of quality targets, data of 13 studies published between 2006 and 2012, each with more than 100 patients and adequate specialisation and experience of the surgeons (5413 patients), data of the prospective multicentric observation study "Quality Assurance - Rectal Cancer" (at the Institute for Quality Assurance in Operative Medicine at the Otto-von-Guericke University at Magdeburg) from 2005 to 2010 (8044 patients) and data of the Department of Surgery, University Hospital Erlangen, from 1998 to 2011 (991 patients) were analysed. The total incidence of operations in the muscularis propria plane of surgery was 5.0 % (721/14 448). Even with adequate specialisation and experience of the surgeon, the frequency of operations in the muscularis propria plane of surgery is higher in abdominoperineal excisions than in sphincter-preserving surgery (8.4 vs. 2.8 %, p < 0.001). Thus, the quality target for the frequency of operations in the muscularis propria plane should be defined as < 5 % for sphincter-preserving procedures and as < 10 % for abdominoperineal excisions.
EVALuna2:15146